Patterns of Snow Drought Under Climate Change: From Dry to Warm Dominance - Chuan Wang; Zhi Li; Nicolas Guyennon; Yaning Chen; Yupeng Li; Qixiang Liang; Yanfeng Di (Geophysical Research Letters)
Abstract Global warming may trigger more frequent snow droughts (SD). SD can result from low total precipitation (dry‐SD), high temperatures leading to less solid precipitation (warm‐SD), or a combination of both (dry‐warm compound SD). Those three SD types threaten ecosystems differently. Nevertheless, the regions dominated by SD types, the transition patterns, and future risks under climate change remain unclear. We investigated the dominance of the three SD types and their transition patterns across historical and future periods. By 2100, compared to 1981, the results project global increases in SD frequency by more than 3‐fold and 4‐fold under SSP2‐4.5 and SSP5‐8.5 scenarios, respectively. Moreover, the share of warm SD is increasing and projected to account for 65% of the three SD types by 2050. Compared to historical period, the probabilities of dry‐warm compound SD and warm SD in the future period is expected to increase by 3.7 and 6.6 times, respectively.